2017
DOI: 10.1111/1756-185x.13150
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of ultrasonography in assessing disease activity in patients with idiopathic inflammatory myopathies

Abstract: Aim: Idiopathic inflammatory myopathies (IIM) comprise a group of rare and heterogeneous diseases difficult to diagnose and follow up. Precise measures for assessing disease activity are not available at the moment. Our objective was to evaluate the usefulness of ultrasonography (US) as a monitoring tool in IIM. Method:The study evaluated IIM patients diagnosed and followed up from 2005 to 2015 in our department. Fifteen patients with a mean age of 52.2 AE 22.09 years and mean disease duration of 4.6 AE 3.20 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 32 publications
(38 reference statements)
0
6
0
Order By: Relevance
“…No differences in PD signal were seen between healthy controls and people with IIM. A single previous published study reported increased PD signal in acute IIM [ 45 ]. A few possibilities could explain this discordance.…”
Section: Discussionmentioning
confidence: 99%
“…No differences in PD signal were seen between healthy controls and people with IIM. A single previous published study reported increased PD signal in acute IIM [ 45 ]. A few possibilities could explain this discordance.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to supporting a diagnosis, ultrasound has potential as an indicator of disease activity in inflammatory myopathy. This is often a clinically difficult question since weakness in these patients may be due to active inflammation, but may also be due to corticosteroid use, chronic atrophy, or a comorbid condition (Sousa Neves et al, 2018). The sensitivity of muscle ultrasound in detecting histopathologically proven inflammatory myopathy has been reported as high as 82.9% (Reimers et al, 1993).…”
Section: Muscle Ultrasoundmentioning
confidence: 99%
“…Muscle edema on NMUS appears to be specific to acute myositis. This is seen as focal or generalized hypoechogenicity and increased muscle thickness (Reimers et al, 1993, Sousa Neves et al, 2018). However, the more common finding appears to be hyperechogenicity with normal or increased muscle thickness, with the increased in echogenicity suspected to be due to inflammation and edema (Mittal et al, 2003, Sousa Neves et al, 2018).…”
Section: Muscle Ultrasoundmentioning
confidence: 99%
“…It can also normalize after start of treatment, paralleling improvement in clinical condition [38]. A recent study with mostly PM/DM patients found that US findings correlated well with disease activity [42]. Stonecipher, et al has described an increase in echo intensity of deltoid, biceps and triceps muscles in patients with DM even when muscle enzymes were normal [36].…”
Section: Dermatomyositis and Polymyositismentioning
confidence: 99%